2008
DOI: 10.1111/j.1751-7915.2008.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate racemase as a target for drug discovery

Abstract: SummaryThe bacterial cell wall is a highly cross‐linked polymeric structure consisting of repeating peptidoglycan units, each of which contains a novel pentapeptide substitution which is cross‐linked through transpeptidation. The incorporation of d‐glutamate as the second residue is strictly conserved across the bacterial kingdom. Glutamate racemase, a member of the cofactor‐independent, two‐thiol‐based family of amino acid racemases, has been implicated in the production and maintenance of sufficient d‐glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 98 publications
(165 reference statements)
2
54
0
Order By: Relevance
“…It has been suggested that subtle structural differences in GR active sites among the different bacterial species weaken the binding of inhibitors in some species resulting in the narrow antibacterial spectrum of the D-Glu-analogue inhibitors (Fisher, 2008). This could be the reason limiting the antibacterial spectrum of the K compounds as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that subtle structural differences in GR active sites among the different bacterial species weaken the binding of inhibitors in some species resulting in the narrow antibacterial spectrum of the D-Glu-analogue inhibitors (Fisher, 2008). This could be the reason limiting the antibacterial spectrum of the K compounds as well.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that the charged groups on these inhibitors adversely affect their permeability properties leading to their narrow antibacterial spectrum. Other factors such as structural differences among GRs from different bacterial species, however, remain possible as has been suggested (Fisher, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme MurI is a glutamate racemase [18], producing d-Glu from the cellular pool of l-Glu for incorporation into growing peptidoglycan [19,20]. MurI operates via a two-base mechanism, wherein conserved cysteine residues in the enzyme active site alternately abstract and donate a proton to opposite faces of the glutamate a-carbon in order to effect racemization [21][22][23].…”
Section: Special Report Combating Resistance: Infectious Diseasesmentioning
confidence: 99%
“…Antimicrobial agents, which represent an important advance in modern medicine for the treatment of infectious diseases, currently interfere with one of four cellular processes: cell wall biosynthesis, protein synthesis, DNA replication and repair, or folic acid coenzyme biosynthesis inhibition (this coenzyme is necessary for the biosynthesis of timine 1 ). Although heralded in the 1940's as the beginning of the end of infectious diseases, during the last 20 years, more of these agents have lost their efficiency due to their abuse in medicine and agriculture.…”
Section: Introductionmentioning
confidence: 99%